Effect of Electronic Word of Mouth, Perceived Service Quality and Perceived Usefulness on Alibaba's Customer Commitment - Rizwan Ali; Fiqh Rifqi Mahisah Wahyu; Didit Darmawan; Eli Retnowati; Utami Puji Lestari (Forum Kerjasama Pendidikan Tinggi, 2022)
Consumer behavior to do online shopping is growing with technological advances. To meet consumer needs for online shopping various e-commerce began to develop. Alibaba is one of the e-commerce services in the world that has emerged in the current digital era that provides various attractive offers and attractive sales products. Alibaba can be reached anywhere and anytime. This study aims to determine how the influence of electronic word of mouth, perceived service quality and perceived usefulness on Alibaba's customer commitment. The population used in this study were Alibaba users. This study used 100 respondents as the research sample. The data will be analyzed using multiple linear regression analysis techniques. The results show that electronic word of mouth, perceived service quality and price perception can have a significant effect on Alibaba's customer commitment.